Improving Students' Critical Thinking in Understanding Texts by Implementing Directed Reading Thinking Activity (DRTA) Strategy - SB, Handayani (Bhandar: Harvesting Community Service in Asia, 2024)
This study examines the application of Directed Reading Thinking Activity (DRTA) strategy in improving students' critical thinking skills when understanding texts. Critical thinking is essential for students to analyze, evaluate, and synthesize information effectively. This study highlights the importance of incorporating interactive reading strategies in educational practices to foster deeper comprehension and critical analysis in students of Akper Kesdam I/BB Padang. The method used in this study is classroom action research with a sample of 41 TK II students who are studying English for Nursing. The learning outcomes of students who obtained completeness in the pre-cycle or pre-test are still included in the category of less than good (very low) with an average value obtained of 56.80 or 24.39%. After conducting cycle I, there was an increase in the average value of 66.20 or 43.90% and after reflection continued to cycle II, the average value of students was 81.20 or 82.92%. It can be concluded that the implementation of the Directed Reading Thinking Activity (DRTA) strategy can improve the students critical thinking in reading. The implications of these findings suggest that educators should adopt the DRTA strategy to improve reading engagement and critical thinking in diverse learning contexts.